Reconstructing historical context. German cities and the case of Lübeck - Michele Caja (Anuari d’Arquitectura i Societat)
The more or less plausible reconquest of the historical image built up over the centuries – violently removed by the war and the infrastructural interventions of the following decades – poses central, inescapable questions in the current debate on historical contexts and on the relationship between old and new, beyond a still too indeterminate notion of authenticity. It is precisely within this image that the reconstruction interventions in Germany, considered here as mature and conscious responses to a new reconstructive phase of historical centres, can be explained. Within the history of reconstruction, they are thus paradigmatic for the questions they raise, but also for the concrete solutions they offer, in their dialectical relationship between copy and reinterpretation. For this reason, they cannot be treated as simple cases of stylistic reconstruction, but need to be assessed as genuine projects of contemporary architecture. The revival of the minute structure of the parcellarium, which has often required the demolition of large building complexes built between the 1960s and 1980s, becomes the common denominator of these recent experiences. The mixed model adopted in these cases is based on the coexistence of Leitbauten and Neubauten – pilot buildings reconstructed in the same way as the original ones and new buildings inspired by the existing ones.